Production of fuel oil from elastomer rubber waste via methanothermal liquefaction. (15th April 2023) - Ahmad, Nabeel; Ahmad, Nauman; Ahmed, Usama; Abdul Jameel, Abdul Gani; Amjad, Um-e-Salma; Hussain, Murid; Arif, Muhammad Maaz
Graphical abstract: Highlights: Rubber waste was converted to bio-oil via methanolysis. 79 % wt% of maximum yield was achieved at 325 °C, 1:1 ratio, and 0.5 h. This yield was considered 21% higher than oil synthesized via pyrolysis. Methanol improved oil properties in term of viscosity, acidity, and GCV. GC–MS showed the high fraction of limonene present in fuel oil. Abstract: The amount of rubber waste is increasing globally due to its use in various industries. This waste rubber do not degrade and it remains in the environment for a long period of time. Polymer recycling industry is in good position to address the issue of rubber waste by converting it into fuel. Fuel oil was produced through the thermal liquefaction of natural rubber polymer, using methanol as a solvent. A kettle batch type reactor was used for the conduction methanothermal liquefaction of natural rubber. Various set of experiments were performed for the synthesis of fuel oil by manipulating the process parameters such as temperature (from 250 °C to 375 °C), methanol to natural rubber ratio (from 0.5/1 to 4/1), and reaction times (from 0.25 h to 1.25 h). The results showed that the highest yield of 79 % of fuel oil was obtained from the methanolysis of natural rubber which was 21.36 % higher than the oil synthesized via pyrolysis of tire rubber. The results of Gas chromatography–mass spectrometry (GC–MS) indicated the presence of limonene about 42 % in oil derived from natural rubber, while the bio-oil obtained from the pyrolysis of tire rubber and natural rubber yields approximately 25 % and 32 % of limonene respectively. Also, the presence of alkyl derived groups and methylene groups were recognized as the supreme leading functional groups present in fuel oil. The elemental analysis showed that in comparison to natural rubber, the high amount of sulfur was present in tire rubber based oil makes it corrosive and toxic.